Effect of Combined Traditional Acupuncture and Applied Kinesiology on Lumbar Diseases - Chang Beohm Ahn (Journal of Acupuncture Research, 2020)
Background Several Korean medical doctors have been practicing applied kinesiology (AK), invented in 1964 by Dr. George J Goodheart, USA. Although the efficacy of traditional acupuncture (TA) and pharmacopucture treatment for lumbar conditions/diseases has been examined, the possible benefits of combining TA and AK have not been reported. Therefore, the aim of this study was to report the effects of combining TA and AK treatment for lumbar disorders using the Japanese Orthopedic Association lumbar score (JOALS) assessment. Methods There were 21 outpatients treated at Samse Korean Traditional Hospital between March 2018 and September 2018, who presented with L4/L5 or L5/S1 root radiculopathy associated with lumbar spinal stenosis (LSS) and lumbar herniation of intervertebral disk (LHID). They were treated 10×(2 sessions per week, for 5 weeks) with TA and AK approaches that included a category block, manipulation or strain/counterstrain treatments. The primary outcome was mainly assessed using the JOALS score which was used before (0 ×), during (5 ×), and after treatment (10 ×). Results There were 19 patients diagnosed with LSS and 2 were diagnosed with LHID. Using the JOALS assessment, TA and AK combined approaches improved the lumbar conditions of all 21 patients after 5 × treatmentsand continued to improve after 10 × treatments (p < 0.001). Conclusion Combined TA and AK treatment was effective in treating spinal conditions/diseases. Prospective, relevant, well-controlled protocols for TA and AK therapies for various conditions are needed.